Menakar Keadilan Restoratif (Restorative Justice) dalam Penyelesaian Tindak Pidana Penyalahgunaan Narkotika - Ganjar Wiyangga; Aturkian Laia (INDO PUBLISHING, 2026)
Drug abuse in Indonesia continues to be dominated by a punitive approach that emphasizes retribution rather than rehabilitation, resulting in inadequate legal protection for drug users as victims of addiction. This study aims to analyze the juridical framework of restorative justice, identify the obstacles to its implementation, and formulate a more progressive legal policy for resolving drug abuse cases. This research employs a normative legal research method using a statutory approach and a conceptual approach. The study relies on primary, secondary, and tertiary legal materials collected through library research and analyzed qualitatively. The findings indicate that the normative foundation for implementing restorative justice has been established; however, its implementation remains constrained by rigid legal provisions, inconsistent interpretation among law enforcement officers, limited capacity of the Integrated Assessment Team, and inadequate rehabilitation facilities. Therefore, regulatory harmonization, strengthened assessment mechanisms, and the optimization of rehabilitation services are necessary to ensure that restorative justice becomes the primary mechanism for resolving drug abuse cases.